Antimicrobial profile of Acinetobacter baumannii at a tertiary hospital in Honduras: a cross-sectional analysis - Julio Cesar Zuniga-Moya; Clerk Annette Caballero; Mariela Loucel-Linares; Mayra Jazmin Benitez; Edoardo Zambrano-Garcia; Lidice Vanesa Fajardo; Julissa Stephanie Paz; Suyapa A Bejarano; Emilio Barrueto Saavedra; Luis Enrique Romero (Pan American Health Organization, 2020)
Acinetobacter baumannii is considered to be a worldwide threat to public health due to its high antimicrobial resistance rates and the severe infections it can cause. Little is known about this pathogen's resistance in Central America. This report aims to describe the antimicrobial resistance profile of A. baumannii at a tertiary hospital in Honduras. The cross-sectional analysis was conducted at the tertiary care laboratory hospital in San Pedro Sula in 2015 - 2017. A total of 113 consecutive microbiological reports were analyzed, comprising 100 individuals from whom A. baumannii was isolated. Epidemiological and microbiological data, including the isolation setting and patient information, were recorded. Prevalence of multi-drug and extensive-drug resistance was assessed according to international standards. The median age of individuals was 22 years (2 - 35 years); female was the predominant gender (53%). The hospital's pediatric wards had the highest number of isolates (n = 48). The most frequent specimen from which A. baumannii was isolated was skin and soft tissue (n = 39). Resistance to carbapenems was reported to be 40.7% among the isolates (n = 46); multi-drug resistant, 35.4% (n = 40); and extensively-drug resistant, 7.1% (n = 8). This report reveals the threat of this pathogen to public health in Honduras and appeals for antibiotic stewardship programs throughout Central America.